2020
DOI: 10.21203/rs.3.rs-114534/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Mid-Market Strategies for Big Data Governance

Abstract: Many data scientists are struggling to adopt effective data governance practices as they transition from traditional data analysis to big data analytics. Data governance of big data requires new strategies to deal with the volume, variety, and velocity attributes of big data. The purpose of this qualitative multiple case study was to explore big data governance strategies employed by data scientists to provide a holistic perspective of those data for making decisions. The participants were 10 data scientists e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…The study emphasized the importance of overcoming cultural, strategic, technological, and process-related challenges to leverage Big Data for competitive advantage. Knapton (2020) explored Big Data governance strategies employed by data scientists in midmarket companies. The study identified key themes such as ensuring business centricity, striving for simplicity, establishing data source protocols, and designing for security.…”
Section: Case Studies: Successful Big Data Strategies In Leading Comp...mentioning
confidence: 99%
“…The study emphasized the importance of overcoming cultural, strategic, technological, and process-related challenges to leverage Big Data for competitive advantage. Knapton (2020) explored Big Data governance strategies employed by data scientists in midmarket companies. The study identified key themes such as ensuring business centricity, striving for simplicity, establishing data source protocols, and designing for security.…”
Section: Case Studies: Successful Big Data Strategies In Leading Comp...mentioning
confidence: 99%